Carbono almacenado en la biomasa de las especies comerciales de un bosque de colina baja en la quebrada Tapaje, distrito de Mazán, Loreto. 2021 - Llerena Panayfo, María del Carmen (2021)
The biomass and the carbon stock in the commercial species of a low-hill forest of the Mazán district, Loreto, Peru were quantified. The data from the forest census of commercial species of the operational plan (PO) 1 of the cutting plot (PC) 5 of the forest concession contract for timber purposes was evaluated 18-LOR-MAY/COM-MAD-2017-021. The results show a biomass of 21 109,87 kg/ha and 29 060 483.78 kg, where A. loretensis (3392,72 kg/ha, 4 670 522,32 kg) and V. lomatophylla (2572,30 kg/ha, 3 541 109,79 kg) report a higher amount of biomass, while C. prieurii (33,51 kg/ha, 46 137,43 kg) and M. balsamum (12,44 kg/ha, 17 119,77 kg) show lower values. The diameter classes from 70 cm to 79 cm (4117,41 kg/ha, 5 668 152,55 kg) and from 110 cm to more (3983,01 kg/ha, 5 483 132,53 kg) contain the highest values of biomass; while the diameter classes from 40 cm to 49 cm (53,74 kg/ha, 73 975,37 kg) and from 50 cm to 59 cm (1510,93 kg/ha, 2 079 989,59 kg) report the lower values of biomass. The carbon stock amounts to 10,55 tC/ha and 14 53024 tC. A. loretensis (1,70 tC/ha, 2335.26 tC) and V. lomatophylla (1,29 tC/ha, 1770,55 tC) report the highest values; while C. prieurii (0,02 tC/ha, 23,07 tC) and M. balsamum (0,01 tC/ha, 8,56 tC) show the lowest values. Diameter classes from 70 cm to 79 cm (2,06 tC/ha, 2834,08 tC) and from 110 cm to more (1,99 tC/ha, 2741,57 tC) contain a greater amount of carbon stock and the diameter classes of 40 cm to 49 cm (0,027 tC/ha, 36,99 tC) and from 50 cm to 59 cm (0,755 tC/ha, 1039,99 tC) report a lower value of carbon stock.